Arguments from Fairness and Extensive Interpretation in Greek Judicial Rhetoric - Könczöl, Miklós (Informal Logic, 2024)
Arguments from fairness as described in Aristotle’s Rhetoric are usually taken to aim at mitigating the strictness of the law or, in terms of procedure, to favour the defendant. This paper considers a more inclusive interpretation, that is, that arguments from fairness can work both ways. In the example given in the Rhetoric, arguments from fairness are directed at a restrictive interpretation of the text. That may not be necessary however. Likewise, fairness may speak for the claimant. Two examples may support this conclusion: a judicial speech by Hyperides, and the doctrine of issues appearing in Hellenistic school rhetoric.